Implementation of Chest Compression for Cardiac Arrest Patient in Indonesia: True or False - Rendi Editya Darmawan; Untung Sujianto; Nana Rochana (Universitas Airlangga, 2021)
Introduction: The highest cause of death is cardiac arrest. Proper manual chest compression will increase survival of cardiac arrest. The aim of this study was to know the implementation of chest compressions for cardiac arrest patient in Indonesia.Methods: This study used a descriptive quantitative design. The samples were nurse and code blue team when performing manual chest compression to 74 patients experiencing cardiac arrest. The sample have body mass index (BMI) > 20. Research was conducted in two hospitals in Java, Indonesia. Implementation of chest compression is measured based on depth accuracy. Depth accuracy of chest compressions was assessed based on the comparison of the number of R waves with a height >10 mV on the bedside monitor with the number of chest compressions performed. The data were analyzed descriptively (mean, median, mode, standard deviation, and variances).Results: Result of this study is the mean of accuracy of compression depth is 75.97%. The result shows accuracy of compression depth on manual chest compression still under the American Heart Association (AHA) recommendation of 80%, because chest compression rate are not standardized. Chest compression rates are between 100-160 rates/minute, while AHA’s recommendations are 100-120 rates/minute. High compression speed causes a decrease in accuracy of chest compressions depth.Conclusion: In conclusion, the implementation of chest compressions in Indonesia if measured based on accuracy of compression depth is not effective. Nurses and the code blue team have to practice considering the use of cardiac resuscitation aids.